2013
DOI: 10.1080/0951192x.2013.812801
|View full text |Cite
|
Sign up to set email alerts
|

Current economic downturn and supply chain: the significance of demand and inventory smoothing

Abstract: The aim of this article is to analyse and quantify the effects of demand and inventory smoothing into supply-chain performance, facing the extreme volatility and impetuous alteration of the market produced by the current economic recession. To do so, we model a traditional serial three-stage supply chain and we test five settings of order smoothing under two shocks in the market demand, and we measure effects in terms of internal process benefits and customer service level of all supply chain partners. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…In the present day, the difference between physically inventory level and system inventory level is not sufficiently understood to explain or predict its effect on performance (Nachtmann et al 2010, Rekik et al 2008b, Rekik 2011, Rekik and Sahin 2012. However, inventory inaccuracy appears to be a significant problem in practice (Kang and Gershwin 2005, Heese 2007, Uckum et al 2008, Hollinger and Adams 2010, Xu et al 2012, Hardgrave 2013, Mersereau 2013, Metzger et al 2013, Bruccoleri et al 2014 In an empirical investigation, DeHoratious and Raman (2008) observed inaccuracies of 65% on 369.567 inventory records collected from 37 leading retailers in USA. In their study, they conclude that these inaccuracies do not only affect retailers' operational performance, but also that of upstream supply chain partners (Kwak and Gavierneri 2014).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the present day, the difference between physically inventory level and system inventory level is not sufficiently understood to explain or predict its effect on performance (Nachtmann et al 2010, Rekik et al 2008b, Rekik 2011, Rekik and Sahin 2012. However, inventory inaccuracy appears to be a significant problem in practice (Kang and Gershwin 2005, Heese 2007, Uckum et al 2008, Hollinger and Adams 2010, Xu et al 2012, Hardgrave 2013, Mersereau 2013, Metzger et al 2013, Bruccoleri et al 2014 In an empirical investigation, DeHoratious and Raman (2008) observed inaccuracies of 65% on 369.567 inventory records collected from 37 leading retailers in USA. In their study, they conclude that these inaccuracies do not only affect retailers' operational performance, but also that of upstream supply chain partners (Kwak and Gavierneri 2014).…”
Section: Introductionmentioning
confidence: 90%
“…In their study, they conclude that these inaccuracies do not only affect retailers' operational performance, but also that of upstream supply chain partners (Kwak and Gavierneri 2014). Inaccuracies and their eventual correction are likely to increase the bullwhip effect by increasing the variability of orders (Gel et al 2010, Bruccoleri et al 2014). The inventory error will propagate through the entire supply chain (Dai and Tseng 2012).…”
Section: Introductionmentioning
confidence: 98%
“…BWE is observed frequently in industries (Chen and Lee, 2012), and it has been estimated that the economic consequences of this phenomenon can be as much as 30% of factory gate profits (Metters, 1997). Moreover, the recent, sudden, severe and synchronized trade collapse has led to an exasperation of BWE on several manufacturing sectors (Dooley et al, 2010;Cannella et al, 2014b). Considering the transmission mechanism of global SCN, this exasperation has created a detrimental ''domino effect'' throughout the world economy.…”
Section: Background: Bwe and Modeling Assumptionmentioning
confidence: 97%
“…This metric reveals an interesting behavior of the divergent SCN: as the structural complexity of the SCN increases (by means of the number of echelons, the number of nodes and/or its divergence) the differences between both scenarios increase and thus, the SCN becomes more vulnerable to unexpected shocks in market demand. (Cannella et al, 2014a), the advocated elimination of intermediatechannels can also be associated to a "structural lean strategy" (Christopher and Holweg, 2011;Holweg, 2007), aimed at reducing the SCN complexity. This is mainly because the impact of the number of nodes and of the divergence of the SCN imposes new challenges in the SCN design effort.…”
Section: ∆=mentioning
confidence: 99%
“…This type of demand has been adopted in theoretical BWE studies in order to model the extreme volatility and impetuous alteration of the market produced by the current economic recession (Cannella et al, 2014a). The simulation platform used in our work is SCOPE (Domínguez and Framinan, 2013), a multi-agent system (MAS) based software platform for the simulation of complex SCNs.…”
Section: Background and Motivationmentioning
confidence: 99%